PELATIHAN PENGGUNAAN COCA DALAM PENELITIAN LINGUISTIK BAGI MAHASISWA JEPANG SEBUAH PROGRAM PENGABDIAN PADA MASYARAKAT KOLABORATIF INTERNASIONAL - Rizdika Mardiana; Dwi Astuti; Muhammad Ali Hamdi; Bambang Nur Alamsyah Lubis; Muchlas Suseno (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
In the era of globalization and rapid digital technological advancement, approaches to linguistic research have undergone significant transformation. One increasingly popular approach is corpus linguistics, which utilizes digital language data to analyze real and contextual language use. To introduce this method to international students, an International Community Service (P2M) program was held in the form of a training session themed "Using Corpus Tools for Linguistics Research." Conducted twice in June 2025, the program featured interactive sessions using corpus tools such as COCA (Corpus of Contemporary American English) and collaborative practice activities like the "Word Frequency Hunt." Participants actively engaged in linguistic data exploration through frequency analysis, collocation, and cross-genre language usage. Survey results indicated that 95% of participants felt motivated to apply corpus linguistics in their studies. This activity is expected to mark the beginning of ongoing international academic collaboration and open opportunities for future face-to-face implementation.